Current Issues of Taiwan's Marine Protected Areas Legal Regime - Adrian Nugraha (Hasanuddin Law Review, 2020)
As an 'Ocean Nation,' it is essential for Taiwan to make efforts to conserve its aquatic zones through marine protected areas (MPAs). Marine protected areas have considered one of the most precise methods of maintaining sustainable ecosystems and restoring fish stocks. This article discusses the legal regime for marine protected areas currently applied and its institutional arrangements in Taiwan. This study emphasizes legal issues in Taiwan's marine conservation efforts. This paper analyzes eight primary legislation relating to marine protected areas in Taiwan. Furthermore, to acquire actual field data, this study conducted interviews with a semi-structured questionnaire in three prominent Taiwan institutions related to their marine conservation task. All data obtained were analyzed and presented qualitatively. The issues of Taiwan's marine protected area legal regime have been identified. First, the main issue in Taiwan is that the legal basis for marine conservation is the legislation applied to land. Second, the existing maritime law regime in Taiwan does not emphasize marine conservation efforts. Subsequently, this article also discusses institutional arrangements related to Taiwan's marine protected areas. This paper also offers possible solutions. Enforcing five key Acts related to marine conservation, particularly the 2015 Act of Coastal Zone Management and strengthening institutional Taiwan's Ocean Affairs Council, are the solutions offered in this study.